British Association of Dermatologists guidelines for the management of adults with delusional infestation 2022. (1st October 2022) - Ahmed, Alia; Affleck, Andrew G.; Angus, Janet; Assalman, Iyas; Baron, Susannah E.; Bewley, Anthony; Goulding, Jonathan M.R.; Jerrom, Richard; Lepping, Peter; Mortimer, Helen; Shah, Reena; Taylor, Ruth E.; et al.
Abstract: The overall objective of the guideline is to provide up‐to‐date, evidence‐based recommendations for the management of delusional infestation (DI) in adults. Linked Comment:  I. Coulson. Br J Dermatol 2022; 187:457 .